BMD130: Mandarin Language for Tourism I / Academy of Language Studies - UiTM, Academy of Language Studies (2016)
This is the first of two-level Mandarin Language programme designed specification for UiTM Hotel Catering Diploma students. This course aims to provide students with communication and interpersonal skills essential for their personal and professional growth in the workplace. Students are expected to learn the process of building and maintaining interpersonal relationships at the workplace. They are provided with an experiential learning opportunity to analyse verbal and non-verbal messages and the role of personal identity in interpersonal communication. The course will emphasize greatly on developing participants oral communication skills in situational contexts through class activities such as role plays, simulations, impromptu speech and other relevant oral tasks. Students are expected to take part in all language activities conducted in class to ensure success in attaining the intermediate level proficiency. In this course, students will be introduced to the Hanyu Pinyin system ( Romanized Mandarin ). In addition, Chinese culture will also be introduced in this course.